ASSESSMENT OF PHARMACOVIGILANCE SYSTEM IN INDONESIA ACCORDING TO WHO PHARMACOVIGILANCE INDICATORS: CHALLENGES AND POSSIBLE SOLUTIONS - Maulidwina Bethasari (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2023)
Due to the potential of Indonesia as a market and a huge number of emerging new products, a comprehensive pharmacovigilance evaluation is critical in overcoming challenges and assure product safety. This article evaluates the current pharmacovigilance establishment in Indonesia in accordance with indicators stated in the manual published by WHO to identify actual challenges and solution. Evidence of compliance with each indicator was based on data published by the Indonesian national agency of drug and food control that can be accessed on the official website. Furthermore, the collected data were categorized and summarized in tables. From the table, evidence of compliance for indicators CST6, CP6-7, and CO3-8 cannot be found on any official website. These indicators are related to a system for reporting therapeutic ineffectiveness and suspected medication errors, the cost and the number of medicine-related hospital admissions and medicine-related deaths, and low human resources and report numbers. Major cause of the issues, which is reflected in the low number of annualy taken actions, is the low number of reports of Adverse Drug Reactions (ADR) which are highly dependent on the Healthcare Professionals’ (HCPs) and industries’ pharmacovigilance competency and system. Improving HCP’s competency and procurement of resources necessary to arrange the required system are considered as effective solutions for attaining a comprehensive pharmacovigilance system. Keywords: Assessment, national agency of drug and food control, pharmacovigilance, WHO Indicators